Respon Pertumbuhan dan Serapan Hara Jagung Ketan pada Dosis Amelioran Plus Mikoriza di Tanah Pasiran - Astiko, W; Fauzi, M Taufik; Muthahanas, I (Seminar Nasional Lahan Suboptimal, 2023)
Astiko W, Fauzi, M. T., & Muthahanas, I. (2023). Growth response and nutrient uptake of glutinous corn on doses of amelioran plus mycorrhiza in sandy soil. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 33-42).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The addition of ameliorant materials containing mycorrhiza to sandy soil can improve the physical, chemical and biological properties of the soil. This can also have an impact on better plant growth response and increased soil fertility. This study aimed to determine the effect of ameliorant plus mycorrhizal doses on the growth response and nutrient uptake of glutinous corn on sandy soil. The experiment was conducted in Moncok Karya, Pejeruk Karya Village, Ampenan District, Mataram City, from May to July 2023. The research used a randomized block design consisting of five treatment, namely D0: control (without ameliorant), D1: dose of ameliorant 5 tons/ha, D2: dose of ameliorant 10 tons/ha, D3: dose of ameliorant 15 tons/ha, and D4: dose of ameliorant 20 tons/ha. The results showed that the treatment dose of 20 tons/ha of ameliorant had a significant effect on increasing the height and number of plant leaves, stover weight per plant, nutrient uptake and mycorrhizal development at 42 days after planting compared to other dose treatments. The best dose of ameliorant that can increase growth response and plant nutrient uptake is 20 tons/ha.